Epistemic/Non‐epistemic Dependence. (20th March 2017) - Zangwill, Nick
Abstract: I foreground the principle of epistemic dependence. I isolate that relation and distinguish it from other relations and note what it does and does not entail. In particular, I distinguish between dependence and necessitation. This has many interesting consequences. On the negative side, many standard arguments in epistemology are subverted. More positively, once we are liberated from the necessary and sufficient conditions project, many fruitful paths for future epistemological investigation open up. I argue that that not being defeated does not make for knowledge. And I argue for the multiple realization of epistemic properties in non‐epistemic properties.